A Survey: Security Challenges of Vanet And Their Current Solution - et. al., R. Hemalatha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vehicles have a very crucial role in our routine life; we use different kinds of transportation in our living world, massive increasing vehicle on the road insisting serious problem such as traffic jam, vehicle congestion, road accidents, the demand for more fuel etc., to subdue the all those problems, the technology has used which is called VANET (Vehicular ad-hoc networks) VANET is self-organized wireless network when it has demanded to make communication between vehicles to vehicles and vehicles to infrastructure. VANET successfully implements the intelligent transportation system (ITS), even the vehicles having short-range networks. Due to the rapid change of network topology, the VANET installation is challengeable on the vehicles. To give a safe drive and reduce car accidents, the communication among drivers of vehicles and roadside devices makes sure that should be authenticated; any wrong modification (or) correction in real-time communication may create system failure and affect road safety. This article provides a brief description of various challenging issues in VANET and presents some existing solutions for these problems. Later, we discussed the current status of research and future goals. With this article, researchers and academicians can have a more detailed VANET and research trends in this emerging field.